Anti-obesity effects of seaweeds of Jeju Island on the differentiation of 3T3-L1 preadipocytes and obese mice fed a high-fat diet. (April 2016) - Kang, Min-Cheol; Kang, Nalae; Ko, Seok-Chun; Kim, Young-Bum; Jeon, You-Jin
Abstract: The seaweeds were collected from the coast of Jeju Island, South Korea. We investigated ethanol extracts from seaweed as potential antiobesity agents by testing their effect on adipogenic differentiation in 3T3-L1 cells. Among the red algae extracts tested, the Plocamium telfairiae extract (PTE) showed the highest inhibitory effect on lipogenesis in adipocytes and, thus, was selected as a potential antiobesity agent. PTE treatment significantly decreased the expression of the adipogenic-specific proteins peroxisome proliferator-activated receptor-γ, CCAAT/enhancer-binding protein-α, sterol regulatory element-binding protein 1, and fatty acid-binding protein 4 compared with that in the untreated 3T3-L1 cells. PTE also inhibited high-fat diet (HFD)-induced obesity in male C57BL/6 mice. Oral administration of PTE significantly reduced the body weight, fatty liver, amount of white adipose tissue, and levels of triglyceride and glucose in the tested animals. Taken together, these data demonstrate that PTE can be developed as a therapeutic agent for obesity. Highlights: We study the anti-obesity effect of Plocamium telfairiae (PTE) in 3T3-L1 cells and in mice fed a high-fat diet. PTE suppressed adipocyte differentiation and lipid accumulation in 3T3-L1 cells. PTE downregulated PPARγ, C/EBPα, SREBP-1c and FABP4 protein expression levels. PTE decreased body weight gain and adipose cell size in HFD-induced obesity in mice.